Sistem Informasi Penentuan Rute Pengiriman Barang di CV ASA Menggunakan Metode Algoritma Genetika - Aditya Pratama Putra; Selviana Yunita (KLIK: Kajian Ilmiah Informatika dan Komputer, 2021)
Transportation is a problem that is often faced by companies in distributing their products. This problem relates to the decision making of product distribution routes that optimize the distance traveled, travel time, travel costs, number of vehicles operated, and other available resources. CV ASA is a company engaged in the distribution of goods which is addressed at Jalan Raya By Pass KM 4,4 Sampit City. The product distribution process carried out by the company is by taking orders. CV ASA stipulates the minimum use of transport capacity is 50% - 60%, but there are still 18 of the 35 travel routes with vehicle capacity usage that is less than 50%, which ranges from 9% to 49%. The problem that occurs in the company is a problem from the Capacitated Vehicle Routing Problem (CVRP) whose initial solution was solved using the Saving Matrix Method and then repaired with Genetic Algorithms